Structural analysis of a plant sucrose carrier using monoclonal antibodies and bacteriophage lambda surface display. - Stolz, Jürgen; Ludwig, Andreas; Stadler, Ruth; Biesgen, Christian; Hagemann, Klaus; Sauer, Norbert (Febs Letters, 1999)
Monoclonal antibodies were raised and selected against recombinant Plantago major PmSUC2 sucrose carrier protein. Epitopes of two monoclonal antibodies (PS2-1A2 and PS2-4D4) were mapped using N-terminally truncated PmSUC2 proteins and a lambda library displaying random PmSUC2 peptides. PS2-1A2 recognizes an octapeptide close to the N-terminus of PmSUC2, PS2-4D4 binds to a decapeptide at the very C-terminus. Analyses of antibody binding to yeast protoplasts with functionally active, tagged PmSUC2 protein revealed that both epitopes are located in cytoplasmic domains of PmSUC2. These results support a model for plant sucrose transporters containing 12 transmembrane helices with the N-terminus and the C-terminus on the cytoplasmic side of the plasma membrane.